PENGARUH KONSELING BERBASIS HADIS TERHADAP PRESTASI BELAJAR PADA MAHASISWI STDI IMAM SYAFI’I JEMBER - Nurul Budi Murtini; Irfan Yuhadi; Emha Hasan Ayatulloh Asyari (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
Learning difficulties usually occur in students with low abilities. Hadith-based counseling is a process of helping the psychological side of students who experience problems in the learning process or learning situations based on the guidance of the Prophet's hadiths. Learning achievement is the result obtained by someone after carrying out learning activities. This research aims to examine the effect of hadith-based counseling on learning achievement. The approach used in this research is a quantitative approach. The population of this study were students at STDI Imam Syafi'i Jember. The total sample was 30 people taken using simple random sampling technique. The instrument used was a questionnaire with a Likert scale. The data analysis technique uses simple linear regression with the help of SPSS version 23. The results of this research show that hadith-based counseling has a significant effect on the learning achievement of STDI Imam Syafi'i Jember students. The magnitude of the influence of hadith-based counseling on student achievement in STDI Imam Syafi'i Jember is 70%. Meanwhile, the remaining 30% is explained by other variables not discussed in this research.